Experimental characterisation of walking locomotion on rigid level surfaces using motion capture system - Dang, Hiep Vu; Živanović, Stana (Engineering structures, 2015)
•A motion capture system was utilised for monitoring human walking locomotion.•Seven walking locomotion parameters were measured on rigid level surfaces.•Data were acquired for 10 test subjects walking at 13 different speeds.•Inter-subject and intra-subject variability were statistically characterised. Low-frequency structures, such as footbridges and long-span floors, are often sensitive to variations in dynamic loading induced by pedestrians. As a result, the design of these structures using traditional deterministic approaches is being replaced by stochastic load models that can accommodate different styles of walking. To inform development and facilitate wider implementation of the new stochastic approaches, a database of experimental data characterising both inter- and intra-subject variability of gait parameters is required. This study aims to contribute to the development of such a database by providing a set of data for walking over rigid level surfaces. The motion capture system Vicon was used for simultaneous monitoring of the kinematic and kinetic gait parameters. Ten test subjects walking at 13 different speeds participated in the experimental programme. Novel experimental data on pacing rate, step length, step width, angular positions of the legs and the trunk, and the force amplitude were collected and statistically characterised. The acquired data are suitable for calibration of the bipedal pedestrian models intended for civil engineering applications.